In vitro Propagation of Cataloglu Apricot (Prunus armeniaca L.) Cultivar Using Apical Node As Explant - Ozdemir, Fethi Ahmet; Gur, Nazmi (Mattioli 1885, 2018)
Apricot (Prumus armeniaca L.) is highly nutritious fruit and micro propagation of apricot plant has high economic value. The current study reports micro propagation of cultivar Cataloglu using apical node explants on Murashige and Skoog (MS) medium containing different combinations of BAP+NAA supplemented with 3% sucrose and solidified with 0.65% agar. The results showed a significant effect of concentrations of BAP+NAA on callus induction, shoot regeneration and their length. Rooting percentage was not affected on all shoots regenerated on any concentration of BAP+NAA. However, number of roots per explants and their length had clear implications of the concentrations of BAP+NAA used for regenerating shoots. Optimum shoot regeneration was noted on MS medium containing 1 mg/1 BAP + 0.25 mg/1 NAA; which were rooted on MS medium containing 1 mg/1 IBA. The rooted plantlets were acclimatized in pots containing soil:sand (3:1) ratio under greenhouse conditions. It is concluded that the study will serve as reference for future apricot breeding studies and genetic transformation studies.
Keywords: Apricot (Prunus armeniaca L.); Cataloglu; micro propagation